Մասնագիտական զարգացումը աշխատավայրից ներս - Աբրահամյան Սիրուն / Abrahamyan Sirun (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
To summarize, it is important to note that professional development is a continuous process where innovations and technologies play a crucial role. The effectiveness and accessibility of library operations must align with ever-evolving educational needs. While digitalization, new technologies, and smart robots are vital, we cannot overlook the role of libraries in shaping a healthy society by serving as centers for the development of educational, cultural, and social skills. Libraries must integrate teaching, collaboration, social development programmes, and activities that encourage individualized approaches. To ensure the efficient functioning of libraries, librarians should engage in training courses, familiarize themselves with various technological programmes, develop management methods, acquire new skills, and work to improve library services.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 2 .- էջ 111-116
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն